INTEGRASI MEDIA DIGITAL INTERACTIVE FLAT PANEL (IFP) DENGAN MANIPULATIF VIRTUAL POLYPAD BERBASIS TPACK UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA MURID SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Noeraini, Lilik; Andaryani, Eka Titi; Avrilianda, Decky; Widiarti, Nuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the potential of integrating the Interactive Flat Panel (IFP) digital media with the Polypad virtual manipulative, based on the TPACK (Technological, Pedagogical, and Content Knowledge) framework, in enhancing elementary school students’ motivation and mathematics learning outcomes through a systematic literature review. The study employed a Systematic Literature Review (SLR) following the PRISMA guidelines. The search was conducted in the Google Scholar, ERIC, Scopus, and Semantic Scholar databases, covering publications from 2021 to 2026. Of the 534 identified articles, 25 met the inclusion criteria and were analyzed thematically. The findings indicate that the use of IFP integrated with TPACK-based virtual manipulatives consistently enhances motivation and mathematics learning outcomes. Success factors include the IFP’s multi-touch interactivity, the flexibility of Polypad’s visual representations, and teachers’ TPACK readiness to synergistically orchestrate technology, pedagogy, and mathematics content. For educational practitioners, these findings recommend that teachers not only invest in mastering technological tools, but also actively develop their TPACK competency through continuous professional training and peer collaboration to optimize the impact of IFP and Polypad integration in mathematics learning.